Determinação do tamanho de gota de emulsões de petróleo por RMN de baixo campo - Morgan, Vinícius Gomes (2014)
The emulsions are a big problem to the petroleum industry for causing serious operational drawbacks such as increasing viscosity, pressure loss and reducing pumping efficiency during production, rising costs and precipitation of paraffinic and asphaltenic compounds. An important property of this system is the droplet size distribution (DSD), which affects the viscosity of emulsions, allows stability studies, separation of the phases and a correct sizing of equipment. At this scenario, the lowfield NMR shows a versatile and effective technique, well-established in the crude oil studies with many applications in this array. In the present study, it was applied to determine the DSD on the W/O emulsions using the DROPTRIG sequence pulse assuming spherical droplets and lognormal distribution, with restricted diffusion Murday and Cots’ model (1968). In the total 51 emulsions were prepared using a solution NaCl 10 g/L, varying the percentage of dispersed phase added to the dehydrated oil, the speed and the time of application of shear in three oils, named 1, 3 and 4. It was shown by laser diffraction technique that three oils had a high capacity to stabilize the droplets during the two first hours after synthesis of the emulsions. The measurements by DROPTRIG sequence was performed in two 2.2 MHz NMR spectrometers and some of that emulsions also was performed on MasterSizer laser diffraction equipment to compare the results. Excellent agreement was achieved between the results of the different techniques and between spectrometers. All the emulsions investigated showed very small droplet diameter (less than 5,53 µm). Difficulties were found to work with emulsions synthesized with crude oil 1, with low quantity of dispersed phase (6,48%), but the results showed the DROPTRIG sequence can be applied to measure DSD of the emulsions even that synthesized by low viscous crude oils with great precision and reliability and measurements that can last about 10 minutes. This is the first work in Brazil determining the droplet size of crude-oil emulsions by low-field NMR and represents a great advance in studies involving these systems in this equipment.